Design/Make: An Alternative Practice to Collaborative Learning in Architecture - Ng, Veronica (International Journal of Asian Social Science, 2018)
Positioned within the call for engaging students’ learning in design-build and collaborative learning, architecture schools are fostering alternative practice in teaching and learning. By studying a real-life case study of the Pavilion NOW project, a three-year initiative (from 2015-2017) curated by Shalini Ganendra Fine Arts, in collaboration with School of Architecture, Building and Design, Taylor’s University, this paper aims to provide an alternative practice for architecture education. This project was implemented for three years from 2015 to 2017, curated by Shalini Ganendra Fine Arts (SGFA) and with participation of approximately a group of 15-20 students from Taylor’s University, School of Architecture, Building and Design. In order to achieve the aim, the case is studied through the reflective lens of the educator, interviews conducted with students, the architects and the curator. This paper will discuss the pedagogical aspect derived from the PavilionNOW initiative that constructs an alternative practice for collaborative learning in design-build programs, and outline its effectiveness and challenges. This paper suggests that an inclusive framework that includes the collaborative network of the architects, the curator, and the educator acts as an enabler towards students’ learning beyond the discipline-specific knowledge and skills; with emphasis on students’ disposition and attitudes that encompasses motivation, innovative thinking, self-management and social competencies, as well as the role of the individual within the discipline, and the society at large.